Simulasi Protokol Routing DSDV Pada Jaringan Vehicular Ad-Hoc Network Di Pekanbaru - Zulkifli Zulkifli; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Traffic accidents often happen in big cities like Pekanbaru city. The accidents are usually caused by some factors such as the sum of the vehicle and the vehicle's speed that exceeds the threshold set. Therefore, technologies that can reduce the occurrence of accidents are needed. One of the technologies is Vehicular Ad hoc Network (VANET). VANET makes all vehicles in a network as nodes to communicate. Routing protocols are required in VANET to deliver packet data efficiently and optimally. In this study, Destination – Sequenced Distanced – Vector (DSDV) was used as routing protocols. DSDV for Pekanbaru city was simulated using SUMO and NS-2 software. This simulation uses urban condition in scenario changes the number of nodes. Network performance parameters was evaluated using Packet Delivery Ratio. The results show a network of VANET designed can work well with Packet Delivery Ratio averaged, 95.59%.Keywords : VANET, DSDV, SUMO, NS-2